Adopsi Inovasi Aplikasi Dompet Digital di Kota Pekanbaru - Muhammad Badri (Inovbiz: Jurnal Inovasi Bisnis, 2020)
This study aims to determine the adoption of digital wallet application innovations in Pekanbaru City, to describe the cashless society transition in Pekanbaru City. This study uses an innovation-decision process model, namely: (1) knowledge, (2) persuasion, (3) decisions, (4) implementation, and (5) confirmation. This research uses a quantitative approach with a descriptive format. This study chose 120 respondents consisting of generations Y and Z, with the consideration that these two generation groups are adaptive to digital technology. Data collection is conducted from November to December 2019. The results of this study, high knowledge stage score especially indicators of smartphone users who are very active. The score of the persuasion stage is relatively high especially on indicators of complexity of digital wallet applications. The decision stage score is relatively high, especially the aspects of trial and preference for digital wallet applications. At the implementation stage, most respondents had already installed and used the digital wallet application for transaction activities. At the confirmation stage, most adopters intend to continue adoption. In general, the adoption of the digital wallet application has a positive impact, such as ease of transaction, practically, there is cashback, discounts, and more secure.